APPLICATION OF GUIDED DISCOVERY LEARNING MODEL WITH A SAINTIFIC APPROACH TO INCREASE STUDENT CREATIVE THINKING ABOUT GLOBAL WARMING MATERIAL AT SENIOR HIGH SCHOOL - KIRANA PAMELA PUTRI, FEBRIN (Inovasi Pendidikan Fisika, 2018)
Creative thinking is the ability to think that involves the ability to develop original ideas and connect the previous concept in a rational way. This research aims to describe the implemetion of learning, increase creative thinking, and the response of students in guided discovery learning model with a scientific approach to the global warming phenomenon material. This research method is done with experimentation method with pre-experimental form and type of design one group pre-test post-test with use one experiment class and two classes of replication. Next, analysis the implementation of the learning is done by observation. Implementation on the three classes are observed from the teacher activity for two meetings was stated well done. Based on the analysis of n-gain creative thinking skills in the experiments classes and replication classes grade increase with high category. Learning which is done get students response very good category. Aspects of creative thinking include originality, fluency, flexibility and elaboration. Creative thinking abilities which get the lowest increase is flexibility. Overall learning by applying the model of guided discovery can increase students ability to think creative.. Keywords: guided discovery, the scientific approach, creative thinking skills, symptoms of                      global warming.